2012
DOI: 10.1111/j.1365-2052.2012.02381.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association analysis and genetic architecture of egg weight and egg uniformity in layer chickens

Abstract: The pioneering work by Professor Soller et al., among others, on the use of genetic markers to analyze quantitative traits has provided opportunities to discover their genetic architecture in livestock by identifying quantitative trait loci (QTL). The recent availability of high-density single nucleotide polymorphism (SNP) panels has advanced such studies by capitalizing on population-wide linkage disequilibrium at positions across the genome. In this study, genomic prediction model Bayes-B was used to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(114 citation statements)
references
References 38 publications
3
111
0
Order By: Relevance
“…In vertebrates, the FTO genotype was shown to be associated with phenotypic variability in body mass index in humans, with the two homozygotes differing 7% in standard deviation (SD) (Yang et al 2012). In laying hens, a QTL region on chromosome 4 was identified that explained 30% and 16% of the genetic variance in mean and within-individual SD, respectively, of egg weight (Wolc et al 2012); and in dairy cattle the phenotypic variability of somatic cell score, an indicator for mastitis, was shown to be determined by many loci, while that with the largest effect explained 3% of the genetic variance in V E (Mulder et al 2013a). It has been argued that findings such as those of Yang et al (2012) can also be explained in terms of a scale effect (Sun et al 2013), but the extreme transformations required are not biologically plausible (Shen and Rönnegård 2013).…”
mentioning
confidence: 99%
“…In vertebrates, the FTO genotype was shown to be associated with phenotypic variability in body mass index in humans, with the two homozygotes differing 7% in standard deviation (SD) (Yang et al 2012). In laying hens, a QTL region on chromosome 4 was identified that explained 30% and 16% of the genetic variance in mean and within-individual SD, respectively, of egg weight (Wolc et al 2012); and in dairy cattle the phenotypic variability of somatic cell score, an indicator for mastitis, was shown to be determined by many loci, while that with the largest effect explained 3% of the genetic variance in V E (Mulder et al 2013a). It has been argued that findings such as those of Yang et al (2012) can also be explained in terms of a scale effect (Sun et al 2013), but the extreme transformations required are not biologically plausible (Shen and Rönnegård 2013).…”
mentioning
confidence: 99%
“…In chickens, many genome-wide association studies (GWAS) were conducted using the Illumina 60K SNP Beadchip. Using this method, major loci associated with growth (Gu et al, 2011;Xie et al, 2012), egg production Wolc et al, 2012), rumpless and ear-tufted traits (Noorai et al, 2012), body composition and meat quality (Liu et al, 2013), resistance to Marek's disease (Li et al, 2013), and immune responses to Newcastle disease virus (Luo et al, 2013) were identified.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro amplify specific DNA sequences with the help of Recently in plant and animal breeding, the concept of QTL affecting the variance of quantitative traits (vQTL) has gained importance because of the increasing importance of uniformity (Wolc et al, 2012). The first of published studies on vQTL was on recombinant inbred lines of maize for economically important traits (Ordas et al, 2008), whereas in animals, researchers failed to detect significant vQTL while working on back fat thickness in pigs (Yang et al, 2011).…”
Section: ) Pcr-based Dna Markersmentioning
confidence: 99%
“…Because of lesser investment in the field of molecular markers, the full potential of MAS is not being capitalized in developing countries. A practical complication analysed for MAS is the loss of relationship between distinct marker allele and favourable trait, when marker is not in proximity of the region to be selected (Fulton, 2012).…”
Section: Scope For Mas In Poultry In Developing Countriesmentioning
confidence: 99%